MODEL DAN STRATEGI PEMBELAJARAN - Sabrun Jamil; Azizurahman Azizurahman; Musthofa Husein; Sarah Salsabila; Shinta Adha Selina (STKIP Subang, 2026)
The success of the learning process in the modern era highly depends on the selection of appropriate and adaptive learning models tailored to students' needs. This study aims to analyze the comparative effectiveness of various innovative learning models, including Problem-Based Learning (PBL), Discovery Learning, cooperative learning (Jigsaw), and Blended Learning, as well as to identify optimization strategies within dynamic classroom environments. The methodology employed is a literature review, analyzing multiple research findings and metaanalyses related to the implementation of these learning models. The results indicate that no single learning model is superior in all situations. PBL is proven effective in enhancing critical thinking skills, whereas Discovery Learning excels in independent conceptual understanding. The Jigsaw model effectively improves collaboration, and Blended Learning offers access flexibility in the digital era. The synchronization of these models with strategies such as differentiated instruction, technology-based media utilization, conducive classroom management, and constructive feedback serves as the primary key to optimizing learning outcomes, triggering intrinsic motivation, and fostering students' active engagement.